Progress in the Research of Features and Characteristics of Mountainous Rural Settlements: Distribution, Issues, and Trends - Yang, Ende; Yao, Qiang; Long, Bin; An, Na; Liu, Yu (Sustainability, 2024)
The study of Features and Characteristics of Mountainous Rural Settlements (RFCMRS) is a key factor in the development of rural settlements during the urbanization process. Mountainous rural settlements, due to their unique mountainous conditions, climate, living environments, and regional culture, are among the important subjects of research for governments and the academic community worldwide. This paper, utilizing the knowledge mapping software CiteSpace (6.2.R3) for co-citation and collaboration analysis, keyword clustering, keyword time zoning, and keyword emergence, analyzes the research trajectory, key issues, and future trends of RFCMRSs. The study finds that current RFCMRS research can be categorized into the following three key issues: “implications of climate change: risks and adaptive responses”, “regional cultural heritage and economic development”, and “ecological conservation and fostering harmonious symbiosis”. Future research will focus on the following three development trends: “risk response based on climate resilience and ecological protection”, “factors of features and characteristics based on regional culture and landscape configurations”, and “human settlements based on low-carbon objectives and sustainable development principles”. Lastly, the paper proposes the following three future research suggestions: “improving the evaluation system for features and characteristics of mountainous rural settlements”, “deepening the study on the evolutionary phenomenon and mechanism for features and characteristics of mountainous rural settlements”, and “exploring the design methods for features and characteristics of mountainous rural settlements based on the concept of sustainable development”.